Hypothermia for neuroprotection in severe traumatic brain injury - Sumit Sinha; Nasim Mansoori (Indian Journal of Neurosurgery)
Traumatic brain injury (TBI) is a common cause of morbidity and mortality worldwide. There has been a constant search for therapeutic modalities in an attempt to reduce this burden, but till date, none of them have proved to have a significant clinical impact. The interest in whole-body hypothermia as a treatment modality for severe TBI arose from enthusiastic experiences with the patients having anoxic brain damage after cardiac arrest. However, despite numerous randomised controlled trials (RCTs) and systematic reviews, its role in improving the outcomes after TBI are still far from being certain to warrant its clinical usage. The concept that hypothermia may be beneficial in improving the outcomes after TBI evolved with the discovery that the final neuronal injury pattern after an ischemic event could be lessened by cooling the brain. Several subsequent animal studies and clinical trials have now been conducted, which have led the Brain Trauma Foundation to issue a Level III recommendation for the use of primary therapeutic hypothermia in the management of TBI. Induced hypothermia should logically be useful in improving the mortality and neurologic outcome after severe TBI. However, the beneficial, effect of hypothermia only exists in high-quality trials, and presently, there is no Level I or Level II evidence. The relative scarcity of high-quality data in this setting entails well-designed large multicentric RCT’s to prove any association if it exists.